2021
DOI: 10.3390/jcm10040765
|View full text |Cite
|
Sign up to set email alerts
|

Tie-2, G-CSF, and Leptin as Promising Diagnostic Biomarkers for Endometrial Cancer: A Pilot Study

Abstract: Preoperative determination of the extent of endometrial cancer (EC) would avoid the complications associated with radical surgery. Screening of patients’ plasma biomarkers might enable a more precise diagnosis of EC and a tailored treatment approach. This prospective case-control monocentric pilot study included 76 postmenopausal women (38 endometrioid EC patients and 38 control patients with benign gynecological conditions), and 37 angiogenic factors (AFs) were investigated as potential biomarkers for EC. AF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 58 publications
(68 reference statements)
2
19
0
Order By: Relevance
“…AFs’ concentrations in preoperative plasma samples of patients with endometrioid EC (n = 38) and control patients with benign gynecological conditions (e.g., prolapsed uterus or myoma; n = 38) were measured using Luminex xMAP™ multiplexing technology. Our discovery study demonstrated significant differences in the plasma levels of six AFs: sTie-2, G-CSF, and leptin were present in different concentrations in EC versus control patients, and IL-8, neuropilin-1 and follistatin differed among different EC subgroups ( 19 ). The roles of these AFs have been described in detail in our recent review paper ( 12 ).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…AFs’ concentrations in preoperative plasma samples of patients with endometrioid EC (n = 38) and control patients with benign gynecological conditions (e.g., prolapsed uterus or myoma; n = 38) were measured using Luminex xMAP™ multiplexing technology. Our discovery study demonstrated significant differences in the plasma levels of six AFs: sTie-2, G-CSF, and leptin were present in different concentrations in EC versus control patients, and IL-8, neuropilin-1 and follistatin differed among different EC subgroups ( 19 ). The roles of these AFs have been described in detail in our recent review paper ( 12 ).…”
Section: Introductionmentioning
confidence: 80%
“…Neuropilin-1 plasma level was higher in patients with type 2 EC (G3) compared to patients with lower grade cancer or controls. Follistatin level was higher in patients with LVI, and IL-8 plasma level was higher in patients with metastases ( 19 ). In this validation study, we further evaluated those six AFs on a larger group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated sTie2 levels have been associated with certain neoplastic and non-neoplastic diseases and have been explored as circulating biomarkers [ 46 ]. However, in our previous study, we detected significantly lower sTie2 plasma levels in patients with the endometrioid type of EC compared to patients with benign gynecological pathologies [ 5 ].…”
Section: Angiogenic Diagnostic and Therapeutic Biomarkersmentioning
confidence: 90%
“…For larger tumors, EC cells must start to produce angiogenic factors (AFs), i.e., special cytokines, which are secreted into the surrounding tissue and nearby vessels, causing angiogenesis and the delivery of nutrients to the cancerous cells. Elevated AF levels can also be detected in the systemic circulation, indicating a potential non-invasive strategy to detect cancer in its early stages [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the procedure is operator dependent, and the different ET cut-offs also affect its clinical utility [6] . Besides TVU, the search for circulating biomarkers to facilitate the early detection of cancer has gained great momentum over the last decade, showing the potential of some blood test techniques at differentiating early stage EC cases from healthy controls, while requiring further verifying [7][8][9][10] . Until now, there are no consensus on protocols for EC screening.…”
Section: Introductionmentioning
confidence: 99%